DEKOLONISASI MANAJEMEN MUTU PENDIDIKAN ISLAM: KRITIK EPISTEMOLOGIS TERHADAP ADOPSI TOTAL QUALITY MANAGEMENT BARAT DAN TAWARAN KERANGKA ALTERNATIF BERBASIS NILAI ISLAM - Ahmad Muqaffi; Siti Julaiha (STKIP Subang, 2026)
This article offers an epistemological critique of the uncritical adoption of Total Quality Management (TQM) in Islamic educational institutions (madrasah) in Indonesia. Using a library research method with a critical-analytical approach, this study identifies three fundamental layers of problematic assumptions embedded in TQM: ontological (human as mere resource), epistemological (quality as measurable output), and axiological (customer satisfaction as the ultimate goal). Drawing on decolonization theory (Quijano, Mignolo, de Sousa Santos) and the Islamization of knowledge project (al-Faruqi, al-Attas), this article argues that the adoption of TQM without epistemological reflection constitutes a subtle form of knowledge colonialism that threatens the integrity of Islamic educational goals. As an alternative, this article proposes a conceptual framework grounded in Islamic values—centered on insan kamil, ihsan, falah, and the maqasid al-shari'ah—as a reconstituted basis for quality management in madrasah. This framework does not wholesale reject TQM, but selectively incorporates compatible elements while reorienting their philosophical foundations.